Text world creation in advertising discourse - Hidalgo Downing, Laura (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This article explores the way in which text worlds are created in advertising discourse by analysing linguistic choices and features of context which are crucial in the determination of specific relations between sender(s) and target audience(s), in particular, deixis and frame knowledge. The argument is that a text world model is particularly adequate for the description of the way in which advertising discourse is processed in an active, dynamic, context-dependent way. In this process, addressees reconstruct the world projected in the discourse according to their own cultural and personal knowledge from the linguistic and visual clues provided in the advertisement.